On Galen's medical rhetoric - Irina PROLYGINA (Hypothekai, 2023)
In ancient Greece, medicine was closely linked to rhetoric as it needed the tools to persuade the audience and logically justify the methods of treatment. During the imperial period, mastery of rhetorical techniques became an essential characteristic of educa-tion and belonging to the intellectual elite who highly valued im-provised public speeches and debates, including those on scien-tific topics. Galen, as one of the brightest and most prolific writ-ers of the Antonine and Severan periods, occupied a key place in this culture of the so-called “Second Sophistic”. However, the study of his style still belongs to the category of desideratum. The difficulty lies mainly in the fact that his compositions are extremely diverse in terms of their volume, genre specificity, and target audience, and in each case, require careful correlation of the text with its context. The question is considered of what modern researchers understand by “Second Sophistic” and what criteria determine whether a particular author belongs to this phenomenon. One of these criteria is paideia — a classical school education in grammar, rhetoric, and philosophy, which provided many common formal features recorded in the writings of Greek and Roman authors of that period. And although Galen does not directly speak about his rhetorical education and skepti-cally comments on the methods of rhetorical persuasion, the list of his works devoted to questions of grammar and rhetoric, which is preserved in his autobiographical writings, testifies to his excellent mastery of the subject. On the other hand, even skimming of his writings points to Galen's expertise in compos-ing so-called “progymnasmata” and his mastery of literary gen-res: narration, eulogy, invective, comparison and description, refutation, etc., which allowed him to become an outstanding physician, polemicist, commentator, and inventor of scientific discourse.